LiNbO3 thin films prepared through polymeric precursor method - Simoes, A. Z.; Zaghete, M. A.; Stojanovic, B. D.; Riccardi, C. S.; Ries, A.; Gonzalez, A. H.; Varela, José Arana [UNESP] (Elsevier B.V., 2003)
Thin films of lithium niobate were deposited on (100) silicon by the polymeric precursor method (Pechini method). Annealing in static air was performed at 500degreesC for 3 h. The films obtained were characterized by X-ray diffraction, scanning electron microscopy and transmission electron microscopy. Electrical characterization of the films pointed to ferroelectricity via hysteresis loop. The dielectric constant, dissipation factor and resistance were measured in the frequency region from 10 Hz to 10 MHz. At 1 MHz, the dielectric constant was 46 and the dissipation factor was 0.043. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: electrical properties; ferroelectrics; Li niobate thin films